The emergence of cost effective battery storage - Stephen Comello (Nature Portfolio, 2019)
It is important to examine the economic viability of battery storage investments. Here the authors introduced the Levelized Cost of Energy Storage metric to estimate the breakeven cost for energy storage and found that behind-the-meter storage installations will be financially advantageous in both Germany and California.